Safety and Efficacy Findings from a Non-interventional Study of a New Hyaluronic Acid/Sorbitol Formulation (GO-ON® Matrix) for Intra-articular Injection to Relieve Pain and Disability in Osteoarthritis Patients - Heisel, J.; Kipshoven, C. (Drug Research, 2013)
This non-interventional study was intended to examine the efficacy and tolerability of intra-articular injections with the GO-ON® matrix, a new viscosupplement product made of non-animal sodium hyaluronate combined with the oxygen free radical scavenger sorbitol, when used in routine clinical practice. A total of 1 147 patients (43.5% male, 53,5% female, 3% missing) aged on average 63.3 years with osteoarthritis were enrolled in 398 centers and treated with the product. The most commonly treated joint was the knee (92.9%) with a Kellgren-Lawrence classification of Grade I (6.7%), Grade II (31.4%), Grade III (48.0%), and Grade IV (13.9%).Most patients (58–66%, imputing for missing data) received 1 injection, 29–40% received 3 injections. Using a Likert scale to asses pain, the mean change in pain due to osteoarthritis was a reduction of 56.5% from baseline (2.61±0.80) to 6 months (1.07±0.86). At baseline, 56.2% of patients reported severe/very severe pain versus 5.9% after 6 months. Accordingly, 6.8% of patients reported no pain/mild pain at baseline vs. 67.1% after 6 months. At baseline, 28.9% reported no pain/mild pain vs. to 66.4% after 6 months. At baseline, 29.1% of patients reported severe/very severe functional impairment vs. 3.9% 6 months after the first injection. The 3 and 6 month results were comparable.Adverse reactions were rare and confined to musculoskeletal and connective tissue disorders. No infections were reported in any treated joints. The results confirm that the GO-ON matrix® treatment is effective and well tolerated in the treatment of symptoms due to osteoarthritis.
Keywords: viscosupplementation; ROS scavenger; rapid onset